The Effectiveness of Bug Bounty Program for Technology Company Ecosystem - Munir, Miftahul (UM Purwokerto Press, 2025)
Bug bounty is one of the programs in the field of Cyber Security with the purpose to finding and uncovering vulnerabilities in technology company ecosystem. Researcher focusing on the security field will play a critical role to the success of bug bounty program with their expertise in security system and deep understanding of the technology. The purpose of this study is to examine the effectiveness of bug bounty and its benefits in improving company security system. Qualitative methods were used for collecting and analyzing the data. The results show the importance of bug bounties as the right solution for developing and maintaining security company ecosystem. It is hoped that this paper can serve as a reference for companies to consider the adoption of this program. In the future, this research can develop further by involving effective communication between researchers and the companies to obtain more up-to-date data.